2008
DOI: 10.1007/s00415-008-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Is REM sleep Behaviour Disorder (RBD) a risk factor of dementia in idiopathic Parkinson's disease?

Abstract: This study shows that RBD and dementia have a significant coincidence in the course of PD, and RBD not only precedes or coincides with the motor signs, but can occur during the course of the progression of the PD, suggesting a degenerative process of the dopaminergic and cholinergic neurons of the brainstem nuclei, progressing at a different pace in each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 30 publications
5
69
0
2
Order By: Relevance
“…Recent investigations detected a higher degree of cognitive dysfunction in PD populations with RBD, including executive deficits [36] visuo-spatial dysfunction, [26,38] and mild cognitive impairment [14]. Marion's' group found a higher risk for developing dementia in PD-RBD patients, although they could not find significant differences between RBD and non-RBD patients on any specific cognitive test [27].…”
Section: Introductionmentioning
confidence: 95%
“…Recent investigations detected a higher degree of cognitive dysfunction in PD populations with RBD, including executive deficits [36] visuo-spatial dysfunction, [26,38] and mild cognitive impairment [14]. Marion's' group found a higher risk for developing dementia in PD-RBD patients, although they could not find significant differences between RBD and non-RBD patients on any specific cognitive test [27].…”
Section: Introductionmentioning
confidence: 95%
“…However, their investigation was limited to non-demented subjects, which probably inadequately depicts the situation in routine care. Other studies have described non-motor symptoms and NPS in smaller, very specialized samples rather than from an epidemiological point of view [27,32]. Second, estimates of the occurrence risk of each of these complications vary widely, possibly due to assessment methods, designs, and samples.…”
Section: Introductionmentioning
confidence: 96%
“…A longitudinal evaluation has indicated that the presence of RBD in PD could be a warning sign for the development of cognitive impairment [115]. Most of the studies showing that PD patients with RBD have more cognitive impairment are cross-sectional, which makes a cause-and-effect relationship difficult to establish [108,116,117]. Previously, visual hallucinations have been described as a common symptom in PD patients with RBD [115].…”
Section: Sleep Disordersmentioning
confidence: 99%